Machinery's handbook pocket companion - Pohanish, Richard P.; McCauley, Christopher J. (Industrial Press, 2020)
The Machinery's Handbook Pocket Companion is a concise yet authoritative, highly useful reference that draws its content from the Machinery's Handbook. Designed as a time saver, the Pocket Companion is an ideal quick resource for anyone in manufacturing, metalworking, and related fields for whom convenient access to just the most basic data is essential. Much of the information has been reorganized, distilled, or simplified to increase the usefulness of this book, while keeping it compact. The Pocket Companion is not intended to replace the new Machinery's Handbook, 31st Edition. Instead, it serves as a handy and more portable complement to the Handbook's vast collection of text, data, and standards. -- Back cover.